One-hour sepsis bundle in patients with sepsis shock: A case report of nursing care implementation - Dian , Rahmawati; Denissa Faradita , Aryani (The Journal of Palembang Nursing Studies, 2024)
Background: Sepsis shock is a critical stage of sepsis characterized by impaired organ function and life-threatening consequences. Optimal management of sepsis shock necessitates a collaborative approach involving an interprofessional team inclusive of Intensive Care Unit (ICU) nurses. Prompt and accurate recognition of its clinical presentation is paramount for critical care nurses to ensure timely and effective intervention. Objective: This case report aims to elucidate the nursing care analysis of sepsis shock patients through the application of the one-hour sepsis bundle. Case: This case study revolves around a 69-year-old female admitted to the ICU due to sepsis shock secondary to pleural effusion and lung tumor. The patient exhibited hallmark indicators of sepsis shock, including hypotension necessitating vasoconstrictive support, fever peaking at 38.8°C, leukocytosis at 36.91 x 10^3/?L, elevated lactate levels at 2.7 mmol/L, and inadequate peripheral perfusion. Nursing diagnosis predominantly focused on assessing the risk of shock in the presence of sepsis and hypotension. The patient underwent immediate implementation of the one-hour sepsis bundle, commencing from the emergency room through ICU admission. Nursing interventions encompassed sepsis screening, continuous hemodynamic monitoring, fluid balance assessment, vigilance in maintaining airway patency, and meticulous infection control measures.  Conclusion: Subsequent to fluid resuscitation and initiation of inotropic and vasopressor support, notable improvements in hemodynamics were observed. However, persistent elevation in lactate levels underscored metabolic dysfunction, necessitating sustained vasopressor support beyond the seventh day of treatment due to refractory shock and multi-organ failure. The adoption of the one-hour sepsis bundle emerges as a recommended guideline for nursing management in sepsis shock patients.